COVID-19-induced disruptions of school feeding services exacerbate food insecurity in Nigeria - Abay, Kibrom A.; Amare, Mulubrhan; Tiberti, Luca; Andam, Kwaw S.; Wang, Michael (International Food Policy Research Institute, 2022)
The COVID-19 pandemic and associated lockdown policies have disrupted education, health, and nutrition services globally, with severe implications for children’s well-being. As the pandemic spread, more than 190 countries implemented countrywide school closures, affecting 1.6 billion children around the world. In addition to the direct effects on learning, these closures affect household food security by interrupting school feeding services.